2014
DOI: 10.1017/s1368980014002237
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid dysfunction with adequate and excessive iodine intake in Hebei Province, People’s Republic of China

Abstract: Objective: To explore (i) the prevalence of thyroid dysfunction in populations with adequate and excessive iodine intakes and (ii) the effect of iodine exposure on the prevalence of thyroid dysfunction. Design: Cross-sectional study was conducted in Hebei in 2010. The population was classified as having adequate or excessive iodine intake according to the iodine concentration in drinking water. Demographic information was collected by questionnaire. Levels of serum thyroid hormones, thyroid autoantibodies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
1
13
1
1
Order By: Relevance
“…Since only one of these reported biomarker values [36], Table 4 tabulates results for thyroid diseases only. The paper by Szabolcs et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since only one of these reported biomarker values [36], Table 4 tabulates results for thyroid diseases only. The paper by Szabolcs et al .…”
Section: Resultsmentioning
confidence: 99%
“…The cause was not assessed in one paper because of an adequate median UIC [40]. Four studies compared high and low iodine status populations [35, 36, 37, 41], three papers described one population with a median or mean UIC of the total population of over 300 μg/L [38, 39, 42], and one paper reported that median UIC was adequate but assessed categories of UIC over 300 μg/L [41]. Regarding study quality, three papers used a regression model [35, 40, 42], of which two used models for some of the outcomes [35, 42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, permanent metabolic effects of excess iodine intake could occur if the iodine source is not detected and discontinued . Excess iodine intake has been reported in China, and among African refugees in Sudan, Algeria, and Somalia, mainly associated with drinking water and the use of iodized salt …”
Section: Introductionmentioning
confidence: 99%